UPAYA MENINGKATKAN KESEJAHTERAAN MASYARAKAT MELALUI KELOMPOK USAHA BERSAMA - Rachmat Setiawan; Paulina Siregar; Suhartini (JURNAL DWIJA KUSUMA, 2023)
Efforts to improve Community Welfare through Joint Business Groups are one of the leading sectors that help the economy of the Indonesian people in general. Therefore it is necessary to maximally develop Joint Business Groups (KUB) with the right development strategy so that in the future it is expected to help improve the welfare of the local community. As is known from the local government, of the many KUBs that are there, only a small number are still running, while others have been discontinued. The results showed that the village of Jogomulyo has a large enough natural resource potential, besides that the location and condition of the vi. Efforts to improve Community Welfare through Joint Business Groups are one of the leading sectors that help the economy of the Indonesian people in general. Therefore it is necessary to maximally develop Joint Business Groups (KUB) with the right development strategy so that in the future it is expected to help improve the welfare of the local community. As is known from the local government, of the many KUBs that are there, only a small number are still running, while others have been discontinued. The results showed that the village of Jogomulyo has a large enough natural resource potential, besides that the location and condition of the village of Jogomulyo has a large enough potential to be developed into a tourist location. On this basis, we, the research team, are trying to find strategies that can be used to develop the KUB in order to improve the welfare of the people of Jogomulyo village. The data collection method that we use is direct observation or observation, interviews and distributing questionnaires to the community and local village officials. The spirit to make breakthroughs in order to achieve better results needs to be supported by all parties and followed by a commitment that the ultimate goal of all this is for the common good, namely to improve the welfare of the Indonesian people in general and especially the people of Jogomulyo village, Tempuran District, Magelang Regency. llage of Jogomulyo has a large enough potential to be developed into a tourist location. On this basis, we, the research team, are trying to find strategies that can be used to develop the KUB in order to improve the welfare of the people of Jogomulyo village. The data collection method that we use is direct observation or observation, interviews and distributing questionnaires to the community and local village officials. The spirit to make breakthroughs in order to achieve better results needs to be supported by all parties and followed by a commitment that the ultimate goal of all this is for the common good, namely to improve the welfare of the Indonesian people in general and especially the people of Jogomulyo village, Tempuran District, Magelang Regency.